Pengaruh Pendidikan Kewirausahaan, Praktik Kewirausahaan dan Motivasi Berwirausaha Terhadap Minat Berwirausaha (Studi Kasus pada Mahasiswa Program Studi Manajemen Universitas Islam Malang) - Wati, Ice Trisna; Sunaryo, Hadi; Rizal, Mohammad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze and determine the effect of Entrepreneurship Education, Entrepreneurship Practices and Entrepreneurial Motivation on Entrepreneurial Interest of Management Study Program Students, University of Malang, Class of 2021. This research is a type of quantitative research. The population of this study is management students class of 2021 with a sample size calculated using the slovin formula of 82 respondents. To solve the problem in this study using SPSS assistance with validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, and t test. The results showed that simultaneously the variables of Entrepreneurship Education, Entrepreneurship Practice and Entrepreneurial Motivation had a significant effect on Entrepreneurial Interest. Partially Entrepreneurship Education has a significant effect on Entrepreneurial Interest, Entrepreneurship Practice has a significant effect on Entrepreneurial Interest, Entrepreneurial Motivation has a significant effect on Entrepreneurial Interest. Keywords : Entrepreneurship Education, Entrepreneursip Practice, Entrepreneurial Motivation, Entrepreneurial Interest